MITIGASI MASYARAKAT TENTANG BENCANA BANJIR DI NAGARI AUR BEGALUNG TALAOK KAECAMATAN BAYANG KABUPATEN PESISIR SELATAN (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2019)
This study aims at the Community Knowledge of Bajir disaster mitigation and community preparedness to Reduce the Risk of Flood Disaster at Nagari Aur Begalung Talaok, Bayang Subdistrict, southern coastal district. Descriptive research method The location of the study was at Nagari Aur Begalung Talaok, Bayang Subdistrict, southern coastal district. Population in the study The sample head of the family used an area probability sample and sample respondents based on the